A Study on Consumer Preference of UPI With Reference to Ahmedabad City - Sakhiya, Krishna; Lakhtariya, Dev; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the associations between age and preferences for various payment methods, particularly focusing on Unified Payments Interface (UPI). Utilizing a quantitative approach, we tested multiple alternative hypotheses to explore how age influences payment preferences and perceptions. Results indicate that younger consumers tend to favor UPI due to its convenience, while older adults exhibit a preference for traditional payment methods such as debit and credit cards. Concerns about security and usability are notably more pronounced among older users, suggesting the need for tailored educational initiatives and user-friendly designs. The findings contribute to existing consumer behavior theories by integrating age as a critical factor in technology adoption. Practical implications emphasize the importance of targeted marketing strategies, enhanced user experiences, and effective communication regarding security features to foster greater acceptance of digital payment systems across all demographics. Recommendations for future research include longitudinal studies, cross-cultural comparisons, and an exploration of emerging technologies in the payment landscape. Understanding these dynamics is crucial for stakeholders aiming to enhance digital payment adoption and ensure inclusivity in the financial ecosystem